Pembelajaran Teater Tradisional Melalui Metode Sosiodrama Pada Kelas X SMA Islam Az-Zahrah Palembang - Dona Pransiska; Hasan Hasan (Universitas PGRI Palembang, 2023)
This study aims to identify and describe the traditional theater learning process through the sociodrama method in class X Islamic Senior High School Az-Zahrah Palembang. This research method uses qualitative methods with data collection techniques, namely observation, interviews and documentation. In the processof collecting data, the researchers directly observed the traditional theater learning process at Islamic Senior High School AzZahrah Palembang, where the subject in this study wasclass X IPA3 withatotalof 20 students. The researcher also directly interviewed the arts and culture teacher and one of the students Sinclass X IPA3.There sult softh is study can be concluded that learning traditional theate rthrough the sociodrama method in class X SMA Islam Az-Zahrah Palembang is going well. This can be seen from there sult sof the evaluation or students'ability to practice traditional the ater infront of the class. For the traditional theater itself, the teacher provides Dulmuluk theater material from South Sumatra. The method used by the teacher is using the sociodrama method in which students can directly practice the script thatwill be played and guided directly by the teacher. In this traditional theater learning, students are happy and enthusiastic because they not only learn theory but can also practice it directly so that students becomemore aware and understand the role that will be played. In addition, students can recognize and preserve the local culture, especially the ater arts. Keywords: Traditional Theatre, Sociodrama Method, Dulmuluk Theater.